2024
DOI: 10.1186/s40104-023-00972-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary Clostridium butyricum and rumen protected fat on meat quality, oxidative stability, and chemical composition of finishing goats

Meimei Zhang,
Zhiyue Zhang,
Xinlong Zhang
et al.

Abstract: Background Clostridium butyricum (CB) is a probiotic that can regulate intestinal microbial composition and improve meat quality. Rumen protected fat (RPF) has been shown to increase the dietary energy density and provide essential fatty acids. However, it is still unknown whether dietary supplementation with CB and RPF exerts beneficial effects on growth performance and nutritional value of goat meat. This study aimed to investigate the effects of dietary CB and RPF supplementation on growth p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
(76 reference statements)
1
1
0
Order By: Relevance
“…Numerous studies have reported that RPF could improve the milk yield of dairy cows [6] but did not influence the ADG in Dorper sheep [10] and beef cattle [18]. However, in the present study, we found that the ADG was greater in the RPF group than in the CON group, which is in agreement with a previous study concerning finishing goats [19]. This could explain how the supplementation of RPF increased the total tract digestibility of crude protein, lipids, or crude fiber in steers [20], ewes [21], and sheep [10].…”
Section: Effect Of Dietary Rumen-protected Fat On Growth Performancesupporting
confidence: 90%
See 1 more Smart Citation
“…Numerous studies have reported that RPF could improve the milk yield of dairy cows [6] but did not influence the ADG in Dorper sheep [10] and beef cattle [18]. However, in the present study, we found that the ADG was greater in the RPF group than in the CON group, which is in agreement with a previous study concerning finishing goats [19]. This could explain how the supplementation of RPF increased the total tract digestibility of crude protein, lipids, or crude fiber in steers [20], ewes [21], and sheep [10].…”
Section: Effect Of Dietary Rumen-protected Fat On Growth Performancesupporting
confidence: 90%
“…Spirochaetota, including Treponema, is a phylum of double-membrane Gram-negative anaerobic bacteria regarded as a pathogenic bacterium. A previous study reported that RPF could improve starch digestibility, resulting in a lower starch content in the RPF group [19]. Furthermore, it was found that the Spirochaetota phylum and Treponema genus existed in starch-rich materials.…”
Section: Microbial Community Composition In the Fecesmentioning
confidence: 89%